The Ion-Translocating NrfD-Like Subunit of Energy-Transducing Membrane Complexes - Calisto, Filipa; Pereira, Manuela M. (Frontiers in Chemistry, 2021)
Several energy-transducing microbial enzymes have their peripheral subunits connected to the membrane through an integral membrane protein, that interacts with quinones but does not have redox cofactors, the so-called NrfD-like subunit. The periplasmic nitrite reductase (NrfABCD) was the first complex recognized to have a membrane subunit with these characteristics and consequently provided the family’s name: NrfD. Sequence analyses indicate that NrfD homologues are present in many diverse enzymes, such as polysulfide reductase (PsrABC), respiratory alternative complex III (ACIII), dimethyl sulfoxide (DMSO) reductase (DmsABC), tetrathionate reductase (TtrABC), sulfur reductase complex (SreABC), sulfite dehydrogenase (SoeABC), quinone reductase complex (QrcABCD), nine-heme cytochrome complex (NhcABCD), group-2 [NiFe] hydrogenase (Hyd-2), dissimilatory sulfite-reductase complex (DsrMKJOP), arsenate reductase (ArrC) and multiheme cytochrome c sulfite reductase (MccACD). The molecular structure of ActC and PsrC, NrfD-like subunits, revealed the existence of ion-conducting pathways. We performed thorough primary structural analyses and built structural models of the NrfD-like subunits. We observed that all these subunits are constituted by two structural repeats composed of four-helix bundles, harboring ion-conducting pathways and containing a quinone/quinol binding site. NrfD-like subunits are the ion-pumping module of several enzymes. Our data impact on the discussion of functional implications of the NrfD-like subunit-containing complexes, namely in their ability to transduce energy.